THE IMPACT OF EARLY MARRIAGE ON PREGNANCY: YOUNG WOMEN'S KNOWLEDGE - Ifna Rosydah; Taty Hernawaty; Imas Rafiyah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Women who were married at a young age and got pregnant had a risk of experiencing complications in pregnancy, and contribute 99% of maternal and infant deaths. Knowledge on the impact of early marriage on pregnancy is needed to prevent an increase of risked pregnancy cases. However, information about the impact of early marriage on pregnancy especially in young women population is limited. This study aimed to determine young women's knowledge about the impact of early marriage on pregnancy in the Margajaya Public Health Center. The design of this study was quantitative descriptive. The population of this research was 81 women who had early marriage, the sample was selected using the total sampling method. Data were collected using a questionnaire with the Gutmann scale and analyzed using frequency distribution. The results of the analysis were categorized as good, sufficient and poor. The results of the study found that most women had good knowledge about the impact of early marriage on pregnancy which was 46 respondents (57%), moderate was 24 respondents (29.6%), and poor were 11 respondents (13.5%). The majority of women had limited understanding about preeclampsia. It was concluded that women's knowledge of early marriage and pregnancy was good, although there was a small number that is moderate and poor. Knowledge of women is less related to preeclampsia and eclampsia, there is a need for health education about preeclampsia and eclampsia for women who had an early marriage.Keywords: Early Marriage, Impact, Pregnancy, Knowledge.